From imagery to revelation: interpretation of the apocalypse in the novel The Idiot by F. M. Dostoevsky and in the film Stalker by A. A. Tarkovsky - Gajdos, Nárcisz (Vilnius University Open Series, 2024)
In the literature dedicated to Andrei Tarkovsky, parallels between the protagonist of the film Stalker and the main character of Fyodor Dostoevsky’s novel The Idiot, Prince Myshkin, have been repeatedly drawn. The aim of this study, based on the analysis of the novel and the film, is to show how Tarkovsky attempted to rethink the main philosophical and religious problems of The Idiot in Stalker, centred on the image, and the meaning of the Apocalypse. The starting point of our study is Hans Holbein the Younger’s painting The Body of the Dead Christ in the Tomb, which appears in both works: as an ekphrasis in the novel and as a visual quotation in the film. The painting and its interpretation play an important role in the formation of apocalyptic images in the inner world of the characters.
Keywords: Tarkovsky; Dostoevsky; The Idiot; Stalker; The Body of the Dead Christ in the Tomb